A paramatric manipulation of central executive functioning - GARAVAN, HUGH PATRICK (Oxford University Press, 2000)
The central executive is both an important and poorly understood construct that is invoked in current theoretical models of human cognition and in various dysexecutive clinical syndromes. We report a task designed to isolate one elementary executive function, namely the allocation of attentional resources within working memory. The frequency with which attention was switched between items in working memory was varied across different trials, while storage and rehearsal demands were held constant. Functional magnetic resonance imaging revealed widespread areas, both prefrontal and more posterior, that differentially activated as a function of a trial's executive demands. Furthermore, areas that differed as a function of executive demands tended to lie adjacent to areas that were activated during the task but that did not so differ. Together, these data suggest that a distributed neuroanatomy, rather than a specific and unique locus, underlies this attention switching executive function.
PUBLISHED
Keywords: Psychology